Gamification For Improving Student Engagement In Software Engineering Subject : A Case Study In UTeM - Ab Hamid, Nur Faiqah (UTeM, 2016)
Software engineering Software engineering subject is a very important to every computer science student as it will give an overview about the principles, techniques and process required for development and construction of computer systems now and then. Nowadays the common traditional teaching and learning in software engineering subjects is quite dull and monotonous subject due to the basic studies about software engineering is mostly on the theoretical part. These drawbacks of the traditional approach affect the software engineering student engagements elements such as in participation, performance and emotional. Since they are not interesting and attractive, it is difficult to attract the students to focus on the learning process. In order to improve and enhance student engagement in software engineering class, there is an attractive approach suggested in this research is known as gamification approach. Gamification approach can be applied to invent a more qualified student to the community. The proposed approach can encourage students to learn software engineering more effectively and proactively. In this study, we got feedback from 59 respondents of software engineering subject student from computer science background and the data analysis was done using SPSS software. From the result, it shows that the engagement elements of participation, performance and emotional have significant effects on the adoption of gamification in software engineering class.